Kualitas Jaringan Wireless Di Cafe Pekanbaru - Elfrida Nova Sartika; Rahyul Amri; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Wireless network is a wireless network that uses air as a transmission medium with a medium in the form of electromagnetic waves. Cafe is a place to relax and talk for all ages (young people and parents) in addition to providing a comfortable place this café also provides wifi network that can be accessed by all café visitors who come. In the café that is an obstacle at this time is the internet connection available is unstable, resulting in visitors who are just logging into the wifi network experiencing difficulties and often long buffering. This is because there is no bandwdith division (bandwidth management) so that usage between users is uneven. To find out the quality of the existing network in the café, measurement of network quality uses Quality of Services (QoS) parameters. QoS is a method of measuring how good the quality of service of an existing network, the parameters used are the packet loss of three users during five days of testing. From the test results, the results of the qualification are obtained according to TIPHON standards, on the value of the first user packet loss to the third user with the highest value, namely on the third user on the third day by 4.02% in the good category and for the lowest value of 2.67% on the second user on the first day in the category is very good. For the average value of the highest packet loss value of 3.43% obtained on the second day with the third index in the Category Bagus, while the lowest packet loss average value of 3.09% is obtained on the first day with the third index included in the Category Good based on the TIPHON standard.Keyword: Wireless, Parameter QoS, Packet loss, TIPHON Standard.